Nothing About Us Without Us: Authentic participation of service recipients in system development. (May 2019) - Kaufman, Joy S.; Schreier, Alayna; Graham, Susan; Marshall, Tim; Bracey, Jeana
Abstract: The involvement of consumers in the planning and development of health services has been encouraged and, in some cases, mandated. This involvement is viewed by many as a democratic or ethical requirement in that consumers have a right to influence services. Connecticut has been working toward the full implementation of a children's behavioral health system of care since 1997 but has lacked the mechanisms needed for family members to have their voices heard or to be full partners at decision-making tables. This paper is a case study that highlights work that has been done to 1) gather systematic feedback from families through the use of participatory research methods; 2) increase family access to data; and, 3) build the capacity of caregivers with the goal of increasing their involvement and leadership at all levels of the system of care. Highlights: The involvement of consumers in the planning and development of health services is encouraged. Involvement of consumers is viewed by many ethical as consumers have a right to influence services they receive. Connecticut has been working to engage family members as full partners at children's behavioral health decision-making tables.